KESIAPAN FISIK DAN PENGETAHUAN REMAJA PEREMPUAN SEBAGAI CALON IBU DALAM MEMBINA TUMBUH KEMBANG BALITA DI KECAMATAN PURWAREJA KLAMPOK KABUPATEN BANJARNEGARA - Fauziah Hanum Nur Adriyani (Viva Medika, 2017)
Abstract Early marriage cases occur in many parts of the world with various backgrounds. It is of concern to the international community in light of the risks posed by forced marriage, early childhood sexual relations, early pregnancy, and sexually transmitted infections. Twenty-one percent of Indonesians are teenagers. Only 11.6% of high school graduates continue to universities, which do not continue to enter the marriage level, whereas marriage at a young age invites a risk that can not be ignored. Those who enter the marriage level, generally have inadequate physical and knowledge readiness, so it needs to be prepared. A mother who has good knowledge will produce good toddlers, especially in the first three years of childhood.This study aims to look at the physical readiness, and knowledge of adolescent girls on toddler growth. The study was a cross-sectional analytic study of adolescent girls at Purwareja Klampok High School. After obtaining research approval, physical examination and blood sampling for hemoglobin examination were performed. Furthermore, respondents fill out the questionnaires to find out their knowledge about toddler growth. Of the 75 respondents, the average age was 17.2 years, the Javanese 93.3% and generally living with the elderly (89%). The largest number of siblings is â‰¥ 3 and the desire to continue college is only 28%. Respondents anemia as much as 65,3%, less nutrition 57,3%, good nutrition 38,7%, nutrition more 2,7%, and obesity 1,3%. Sources of information related to the problem of developing newborn toddlers only 61.3% comes from formal sources of parents, teachers and health workers. Knowledgeable teens were 30.7%, knowledge was 48%, and knowledge was less 21.3%. The conclusion in this study is more than half of adolescent (65,3%) have anemia incidence, and malnutrition amount 57,3% so that level of physical readiness of adolescents become mother candidate very less. Keywords: physical readiness, knowledge, youth